Analysis of Cost and Time Performance for Rehabilitation of Ws Brantas Retention Basin Using the Earned Value Method - Purbo, Atma Djendra; Wulandari, Esti; Nugroho, Laksono Djoko (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This research analyzes the cost and time performance of the WS Brantas reservoir rehabilitation project using the Earned Value method, addressing challenges such as cost overruns and schedule delays. The objectives include identifying cost and schedule deviations through the Schedule Performance Index (SPI) and Cost Performance Index (CPI) indicators, and evaluating the method's effectiveness in enhancing project management efficiency. Employing a qualitative descriptive approach, data were collected from nine project sites across Jombang, Tulungagung, and Blitar Regencies over six months, utilizing MS Project 2016 for analysis. Findings reveal significant deviations, with projects like Embung Kerjen incurring additional costs of Rp15,816,784 and an SPI of 0.66. The leading causes of delays included terrain constraints, material delays, and changes in work volume. The study underscores the importance of the Earned Value method as a standardization tool for project supervision, suggesting that its integration with project management technology can improve accountability and efficiency in budget use. This research provides valuable insights for academics and practitioners, offering practical solutions to common project management challenges and assisting government stakeholders in enhancing project supervision standards. By demonstrating the applicability of the Earned Value method in a government context, this study contributes to the development of effective infrastructure management strategies in Indonesia.